The Big Show - Babias, Marius; Fuenmayor, Jesús; González, Julieta Elena; Peeters, Wim; Vermeiren, Gerrit (Antwerpen : NICC (Nieuw Internationaal Cultureel Centrum), 2002)
The Idea for The Big Show grew out of lively discussions with Philip Aguirre, Carla Arocha, Philippe Pirotte and Luc Tuymans. Following the three part exhibition The Big Show (NICC, Antwerp April - November 2001), this publication continues the exhibition's outlines to approach issues of exoticism, collective memory, globalization, utopia and alterity in a demanding way. The Big Show is inevitably part of a climate of post-colonial and global cultural interests, without identifying itself totally with them. Rather the series of exhibitions and this publication form a searching interrogation of the ways in which decolonization and globalisation can be seen in the context of a wider debate surrounding cultural production and representation, without thereby having to lead to an iconoclasm of the center of image production. The Big Show chooses to approach globalization indirectly from three different views. The first path is historical, retracing globalization to a highly problematic post-colonial mentality, with two specific bodies of work by Tshibumba Kanda Matulu and W. Eugene Smith. A Congo Chronicle - a Man of Mercy highlights the complexities surrounding colonial memory. The second chapter Healing traces that trauma - as part of a larger cluster that defines our conceptions of globalization - to a broader cultural present, Healing simulates the gathering of all elements that would allow for shifts in collective memory to be reconstructed. Part three Demonstration Room, Ideal House is utopian, the revolutionary potential of the house and the city are reconsidered from the specific situation of Latin America, but still within a broader international context, rethinking the evolutionary potential present there in actuality or rhetorically.
Lwimba, Tinda ; Burozi ; Smith, William Eugene ; Kalume ; Dekab ; Tshibumba Kanda Matulu ; Bijl, Guillaume ; Davis, Mike ; Doll, Tatjana ; Beuys, Joseph ; Duchamp, Marcel ; Slominski, Andreas ; Yoshihara, Jiro ; Motonaga, Sadamasa ; Shiraga, Kazuo ; Marshall, Kerry James ; Fischli, Peter ; Weiss, David ; Douglas, Stan ; Mikhailov, Boris ; Keiser, Daniela ; Sugimoto Hiroshi ; Piper, Adrian ; Darmawan, Ade ; Hanssen, Karin ; Weiner, Lawrence ; Graham, Rodney ; Robijns, Gert ; Carlos, Isaac ; Jozefowicz, Katarzyna ; Grundmann, Gesine ; Arocha, Carla ; Lupini, Mauricio ; Gillick, Liam ; Alÿs, Francis ; Best, Anna ; Bruggemann, Stefan ; Bunimov, Mariana ; Cuevas, Minerva ; Deleu, Luc ; Fernández, José Gabriel ; Framis, Alicia ; Garaicoa, Carlos ; Gerdel, Alexander ; Graham, Dan ; van Heeswijk, Jeanne ; Hernández-Diez, José Antonio ; Kuri, Gabriel ; Atelier van Lieshout ; Lopez, Diana ; McBride, Rita ; Molina, Carlos Julio ; Neto, Ernesto ; Perna, Claudio ; Ramirez-Jonas, Paul ; Sachs, Tom ; Schneider, Karin ; Téllez, Javier ; Vega, Sergio
Engels
Nederlands & Engels
The Big Show : A Congo Chronicle - A Man of Mercy, 15 April - 3 June 2001, The Big Show : Healing, 24 JUne - 2 September 2001, . The Big Show : Demonstration Room : Ideal House, 23 September - 25 November 2001. A Congo Chronicle was previously shown at the Museum for African Art, New York (1999). The exhibition was conceived by Bogumil Jewsiewicki in collaboration with the Museum for African Art, New York. A Man of Mercy : Africa's Misery Turns Saintly Albert Schweitzer, into a Driving Taskmaster was conceived by W. Eugene Smith as a photo essay, published in Life magazine, XXXVII 20 (November, 15, 1954), 161-172. Curators : Jesus Fuenmayor and Julieta Elena González. Demonstration Room : Ideal House was previously shown at the Museo Alejandro Otero, Caracas (2000) and Apexart, New York (2001).
boek
Keywords: Afrika; Congo; Zaïre